2020
DOI: 10.1039/d0tc00857e
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline rubrene via a novel process and realization of a pyro-phototronic device with a rubrene-based film

Abstract: A single-step solvent-free process for crystalline rubrene film where surface layer polarization results in the pyro-phototronic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…[23][24][25] The organic rubrene crystal usually exhibits the largest hole mobility (µ h ) of 40.0 cm 2 •V −1 •s −1 , which is traced back to the light effective mass and delocalized nature of the holes in the highest occupied molecular orbital (HOMO) of rubrene crystal. [23,[25][26][27] In theory, integration of such an organic rubrene crystal with traditional Si semiconductor can provide the possibility of forming a high-quality organic/inorganic van der Waals heterostructure with the type-II (staggered) band alignment due to the transfer behaviors of majority carriers on the interface. [28,29] Furthermore, the interlayer electron excitons can be realized in this organic/inorganic hybrid heterostructure of rubrene/Si with much longer lifetime because of the type-II band alignment configuration.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] The organic rubrene crystal usually exhibits the largest hole mobility (µ h ) of 40.0 cm 2 •V −1 •s −1 , which is traced back to the light effective mass and delocalized nature of the holes in the highest occupied molecular orbital (HOMO) of rubrene crystal. [23,[25][26][27] In theory, integration of such an organic rubrene crystal with traditional Si semiconductor can provide the possibility of forming a high-quality organic/inorganic van der Waals heterostructure with the type-II (staggered) band alignment due to the transfer behaviors of majority carriers on the interface. [28,29] Furthermore, the interlayer electron excitons can be realized in this organic/inorganic hybrid heterostructure of rubrene/Si with much longer lifetime because of the type-II band alignment configuration.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, while the majority of pyroelectrics used to date have been based on noncentrosymmetric crystals, there is potential to engineer the interface, where the number of atoms can be too small to form a sufficiently thick polar layer for the accumulation of neutralization and depolarization screening charges. In this context, recent studies have shown that centrosymmetric crystals can also exhibit pyroelectric effects at their surfaces/interfaces, [84,[122][123][124][125] revealing a new route to combine plasmonic and pyroelectric effects. It is worth considering the electrochemical interactions between the plasmonic and pyroelectric constituents, where these interactions provide intriguing opportunities for photo-catalysis, [108] bio-applications, water splitting, and water treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced surface roughness of crystalline OS layers have been obtained by polymer-smoothing techniques [ 14 ]. The solvent-free fabrication of a composite film, consisting of crystalline RB and polymerized aniline, was reported by Gogoi et al [ 15 ], who applied a 13.7 MHz RF discharge for plasma polymerization of the aniline-RB vapor mixture at low pressure (2 × 10 − 2 Torr) and demonstrated an optoelectronic device with crystalline RB responsible for a coupled effect of pyro-phototronic and photovoltaic processes.…”
Section: Introductionmentioning
confidence: 99%